Design is not for the weak: on the use in design education - Ober, Maya (Arcos Design, 2022)
Situated interdisciplinary between Anthropology of Education, Gender Studies, and Critical Design Studies, this essay looks at the idea of use and usability in design education. Engaging in dialogue with Sara Ahmed’s philosophical exploration on use and bringing it to the field of design education, I use auto-ethnographic methods to explore micro-politics of hegemonic design pedagogy and its influence on students’ subjectivities in the everyday. Furthermore, I follow feminist traditions that lend importance to mundane daily activities as socio-political configurations through the prism of ethnographic thick descriptions. Finally, in this ethnographic exploration I attempt to open the discussion around use, usability, and usefulness to explore further how asking Ahmed’s question “what’s the use” could unfold new possibilities for radical recentering of design education.